2022
DOI: 10.1021/acs.jpclett.2c02612
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Predicting Chemical Potentials of Multifunctional Organic Compounds in Atmospherically Relevant Solutions

Abstract: We have trained the Extreme Minimum Learning Machine (EMLM) machine learning model to predict chemical potentials of individual conformers of multifunctional organic compounds containing carbon, hydrogen, and oxygen. The model is able to predict chemical potentials of molecules that are in the size range of the training data with a root-mean-square error (RMSE) of 0.5 kcal/mol. There is also a linear correlation between calculated and predicted chemical potentials of molecules that are larger than those includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The quantum machine learning (QML) program employs ML to model molecular quantum chemistry (QC) properties (e.g., electronic energies). Several studies ,, have shown that kernel ridge regression (KRR) can accurately model chemical properties, even when trained on relatively small training databases. In our previous study, we used QML and KRR to predict electronic binding energies (calculated at the ωB97X-D/6-31++G(d,p) level of theory; further referred to as DFT) for the SA–water system, where the binding energy is defined as follows. normalΔ E el = E el cluster prefix∑ E el monomer We showed that, due to correlation of binding energies between DFT and some low level of theory (in our case semiempirical GFN1-xTB, , further abbreviated as XTB), the low level of theory can be used to improve the accuracy of the ML model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantum machine learning (QML) program employs ML to model molecular quantum chemistry (QC) properties (e.g., electronic energies). Several studies ,, have shown that kernel ridge regression (KRR) can accurately model chemical properties, even when trained on relatively small training databases. In our previous study, we used QML and KRR to predict electronic binding energies (calculated at the ωB97X-D/6-31++G(d,p) level of theory; further referred to as DFT) for the SA–water system, where the binding energy is defined as follows. normalΔ E el = E el cluster prefix∑ E el monomer We showed that, due to correlation of binding energies between DFT and some low level of theory (in our case semiempirical GFN1-xTB, , further abbreviated as XTB), the low level of theory can be used to improve the accuracy of the ML model.…”
Section: Methodsmentioning
confidence: 99%
“…The quantum machine learning (QML) program 45 employs ML to model molecular quantum chemistry (QC) properties (e.g., electronic energies). Several studies 42,46,47 have shown that kernel ridge regression (KRR) can accurately model chemical properties, even when trained on relatively small training databases. In our previous study, 42 we used QML and KRR to predict electronic binding energies (calculated at the ωB97X-D/6-31++G(d,p) level of theory; 48 further referred to as DFT) for the SA−water system, where the binding energy is defined as follows.…”
Section: Methodsmentioning
confidence: 99%
“…30 In solvent water, the number of intramolecular H-bonds correlates with the pseudo-chemical potential. 37 However, the calculated mixtures contain non-polar organic compounds and the most favorable conformers may not be the same in polar and non-polar solutions. Here, the conformers for COSMO therm calculations were therefore selected using their pseudo-chemical potentials, instead of their intramolecular H-bonding.…”
Section: Methodsmentioning
confidence: 99%
“…The pseudo-chemical potentials were predicted using a machine learning model. 37,41 200 lowest pseudo-chemical potential conformers in each of the two solvents (at most 400 conformers) were selected for density functional theory calculations using the COSMO conf program. 42,43…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation